Anxiety during the COVID‐19 pandemic in prisoners who had high risks to suffer from mood disorders: A longitudinal study before and during the COVID‐19. (30th June 2022) - Zhang, Shuqi; He, Jin; Yang, Qingzhen; Du, Yizhi; Xiao, Weixia; Gao, Jindi; Li, Hengfen
Abstract: We compared the anxiety levels in prisoners before and after the COVID‐19 outbreak and analyzed the causes of the changes in anxiety. The first survey was conducted in October 2019 (T0), and the second was conducted in March 2020 (T1). Generalized anxiety disorder‐7 (GAD‐7), Patient Health Questionnaire‐9, and Insomnia Severity Index scales were selected to assess the quality of emotion and sleep among prisoners ( N = 803). Three subjective questions were asked to evaluate prisoners' personal feelings on the COVID‐19. Paired Samples T ‐test, Binary, and Multivariate Logistic Stepwise Regression were used to analyze the data. GAD‐7 scores decreased at T1 ( p < 0.001). For the prisoners without anxiety at T0 ( n = 480), GAD‐7's mean value at T1 raised ( p < 0.001), whereas the mean value decreased ( p < 0.001) for the prisoners with anxiety at T0 ( n = 323). For the prisoners without anxiety, shorter years of education (OR = 0.843), COVID‐19 (OR = 4.936), severer depression at T1 (OR = 1.683), and severer insomnia at T1 (OR = 1.134) were associated with the new onset of anxiety. For the prisoners with anxiety, anxiety was alleviated in 71.2% and exacerbated in 10.5% at T1. For the alleviators, severer depression at T1 (OR = 0.667) and COVID‐19 (OR = 0.258) were associated with anxiety unrelief; severer anxiety at T0 (OR = 1.343) was associated with anxiety alleviation. For the exacerbators, severer anxiety at T0 (OR = 0.517) was associated with anxiety unaggravation; severer depression at T1 (OR = 1.196), COVID‐19 (OR = 22.882), and severer depression at T0 (OR = 1.181) were associated with anxiety exacerbation. At the outbreak of COVID‐19, prisoners' anxiety was reduced. The main factor was the baseline anxiety levels. That may be related to prison management and the Downward Social Comparison.